The mediating role of English learning motivation between socioeconomic status and pragmatic awareness - Xiaomeng Hui; Yuqing Chen (Frontiers in Psychology)
Socioeconomic status (SES) has received great attention in learning a second or foreign language (SL/FL). However, little research has investigated the association between SES and SL/FL pragmatic learning, let alone the influencing pathways of SES on SL/FL pragmatic awareness (PA). Therefore, this research aimed to address the link between learners’ SES and PA with the mediating effects of learning motivation based on the L2 motivation self-system (L2MSS) theory by surveying 292 Chinese EFL university students. Structural equation modeling analyses indicated that: (1) SES had no significant effect on ought-to L2 self and intended learning efforts; (2) ought-to L2 self and intended learning efforts had significant predictive effects on PA; (3) SES positively and directly predicted EFL learners’ PA; and (4) ideal L2 self, attitudes toward L2 community, and attitudes toward learning English mediated the relationship between SES and Chinese EFL learners’ PA significantly.